APPLICATION OF SCIENTIFIC MANAGEMENT PRINCIPLES FOR EFFECTIVE MANAGEMENT OF HIGHER INSTITUTIONS IN NIGERIA - Suleiman, Yusuf; Abdulrasheed, Jimoh; Amin, Sani Ibrahim; Abubakar, Yusuf Abiola (Journal of Human Capital Development (JHCD), 2018)
For resources allocated to organization to be appropriately managed, it requires the dexterity of dynamic and focused people who are versed with various management theories and principles. It is against this background that this study examines the need for the application of Fredrick Wislow Taylor’s scientific management principles for efficient and effective management of higher institutions (universities, colleges of education and polytechnics) in Nigeria. The study highlighted lack of proper implementation of good educational policies, lack of adequate funding, misappropriation of funds, brain drain and poor monitoring and evaluation as some of the major problems inhibiting against higher institutions in Nigeria. To ensure that the challenges are addressed, the study suggests the need for proper application of Wislow Taylor’s scientific management principles (planning, organising, staffing, budgeting and controlling) for efficient and effective management so that the goals and objectives of higher institutions in Nigeria can be achieved. KEYWORDS: Management, education, higher institutions, Nigeria